2014
DOI: 10.1016/j.ajpath.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The Niche Component Periostin Is Produced by Cancer-Associated Fibroblasts, Supporting Growth of Gastric Cancer through ERK Activation

Abstract: Overexpression of periostin (POSTN), an extracellular matrix protein, has been observed in several cancers. We investigated the importance of POSTN in gastric cancer. Genome-wide gene expression analysis using publicly available microarray data sets revealed significantly high POSTN expression in cancer tissues from stage II-IV gastric cancer, compared with background normal tissues. The POSTN/vimentin mRNA expression ratio was highly associated with gene groups that regulate the cell cycle and cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 47 publications
7
85
0
Order By: Relevance
“…Additionally, it may be possible to predict, prevent and treat peritoneal metastasis by targeting these molecules. Previous studies have primarily focused on the characteristics of malignant cancer cells, but an increasing number of studies have focused on the tumour microenvironment, particularly milky spots and the tumour stroma (54,64). Milky spots are specific sites for peritoneal metastasis and numerous studies have demonstrated that milky spots are the first metastasis location for free cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it may be possible to predict, prevent and treat peritoneal metastasis by targeting these molecules. Previous studies have primarily focused on the characteristics of malignant cancer cells, but an increasing number of studies have focused on the tumour microenvironment, particularly milky spots and the tumour stroma (54,64). Milky spots are specific sites for peritoneal metastasis and numerous studies have demonstrated that milky spots are the first metastasis location for free cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Periostin (POSTN), produced by fibroblasts, participates in the adhesion and migration of epithelial cells (66). Kikuchi et al (64) reported that POSTN is secreted by CAFs and enhances the proliferation of gastric cancer cells via the activation of ERK. In vivo investigation has further demonstrated that co-inoculation of gastric cancer cells with fibroblasts expressing POSTN facilitates tumour formation (64).…”
Section: Promotion Of Metastasis By Cafmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased expression of POSTN has been observed in various tumor types, including breast [44,48,[56][57][58], NSCLC [27,49,[59][60][61][62], colorectal [19,29,63], stomach cancers [64][65][66][67][68], pancreatic [32,69], prostate [70][71][72][73][74][75], ovarian cancer [76][77][78][79], and glioblastomas [80][81][82] (Table 1).…”
Section: Periostin Expression In Different Types Of Tumorsmentioning
confidence: 99%